Analyses of karyotype by G-banding and high-resolution microarrays in a gender dysphoria population - Fernández, Rosa; Guillamón, Antonio; Gómez-Gil, Esther; Esteva, Isabel; Almaraz, Mari Cruz; Cortés-Cortés, Joselyn; Lamas, Beatriz; Lema, Estefanía; Pásaro, Eduardo (Genes and Genomics, 2018)
Gender Dysphoria is characterized by a marked incongruence between the cerebral sex and biological sex. To investigate the possible influence of karyotype on the etiology of Gender Dysphoria we carried out the cytogenetic analysis of karyotypes in 444 male-to-females (MtFs) and 273 female-to-males (FtMs) that attended the Gender Identity Units of Barcelona and Málaga (Spain) between 2000 and 2016. The karyotypes from 23 subjects (18 MtFs and 5 FtMs) were also analysed by Affymetrix CytoScan™ high-density (HD) arrays. Our data showed a higher incidence of cytogenetic alterations in Gender Dysphoria (2.65%) than in the general population (0.53%) (p < 0.0001). When G-banding was performed, 11 MtFs (2.48%) and 8 FtMs (2.93%) showed a cytogenetic alteration. Specifically, Klinefelter syndrome frequency was significantly higher (1.13%) (p < 0.0001), however Turner syndrome was not represented in our sample (p < 0.61). At molecular level, HD microarray analysis revealed a 17q21.31 microduplication which encompasses the gene KANSL1 (MIM612452) in 5 out of 18 MtFs and 2 out of 5 FtMs that corresponds to a copy-number variation region in chromosome 17q21.31. In conclusion, we confirm a significantly high frequency of aneuploidy, specifically Klinefelter syndrome and we identified in 7 out of 23 GD individuals the same microduplication of 572 Kb which encompasses the KANSL1 gene.
Keywords: 17q21.31 microduplication; aneuploidy; gender dysphoria; KANSL1; klinefelter syndrome; Scopus